Polypharmacy and potentially inappropriate medication use is highly prevalent in multiple myeloma patients and is improved by a collaborative physician–pharmacist clinic. (April 2020) - Sweiss, Karen; Calip, Gregory S; Wirth, Scott; Rondelli, Damiano; Patel, Pritesh
Objective: To compare polypharmacy and potentially inappropriate medication use in multiple myeloma patients receiving care under a traditional, physician-managed, or collaborative physician–pharmacist clinic. Design: Retrospective chart review. Setting: Urban academic cancer center. Data source: Computerized electronic record. Patients: Forty-four patients in the traditional physician-managed clinic and 57 patients in the collaborative physician-pharmacist clinic. Measurements and main results: Patients in the collaborative clinic took fewer medications on average (9 vs. 7, p = 0.045). Although the median number of myeloma-related medications was higher (2 vs. 4, p < 0.0001), the number of non-myeloma-related medications was lower (7 vs. 3, p < 0.0001) in the collaborative clinic. Polypharmacy rates were high in both clinics (93% vs. 84%, p = 0.22). However, the collaborative clinic had a lower rate of polypharmacy of non-myeloma medications (71 vs. 33%, p = 0.0003), including both minor (five to nine medications, 48 vs. 28%, p = 0.06) and major (≥10 medications, 23 vs. 5%, p = 0.02) polypharmacy. Minor polypharmacy of myeloma-related medications was higher in the collaborative clinic (32 vs. 2%; p = 0.0002). Multivariate analysis showed a reduced risk of having a higher number of medications (Relative risk (RR) 0.79, 95% confidence interval 0.67–0.93; p = 0.004), a lower risk of having any polypharmacy of non-myeloma-related medications (RR 0.41, 95% confidence interval 0.25–0.67; p < 0.001) and a lower risk of receiving potentially inappropriate medication (RR 0.62, 95% confidence interval 0.41–0.95; p = 0.029) in the collaborative clinic. Conclusions: Multiple myeloma patients have a high rate of polypharmacy but comanagement with a pharmacist reduced the number of all medications, but in particular the number of non-myeloma-related medications.